An Implementation of Online Blended Learning Training and Learning Management System in The Covid-19 Pandemic - Hakim, Khaled Maulana Ihya Arief Rakhman; Arbarini, Mintarsih; Raharjo, Tri Joko (Journal of Nonformal Education, 2022)
The existence of the COVID-19 pandemic outbreak has caused a high level of open unemployment in Indonesia. To overcome this problem, the Indonesian Ministry of Manpower held training to be given to people who do not have the skills and want to develop their skills. There are two kinds of training provided, namely blended learning training and online learning management system. This study aims to describe (1) the implementation of blended learning-based online training and LMS (2) Obstacles and solutions to the implementation of blended learning and LMS training. The research method used is a qualitative method. The research subjects included 2 training program managers, 2 training instructors, 2 training participants. The data collection techniques included in-depth interviews with 2 training program managers, 2 training instructors, 2 trainees, observation, and documentation related to the implementation of blended learning and LMS training. The validity of the data used triangulation of sources. The data analysis techniques consist of data collection, data reduction, data presentation and drawing conclusions. The results of the study explain that blended learning training was carried out with a portion of 30% online and 70% offline, while LMS was carried out online by combining an e-training platform as a learning support. The obstacle in implementing this training was the internet network connection. The solution provided was the training instructor reviewed the training material during offline training. In conclusion, BBPLK Semarang is one of the institutions that implement blended learning and LMS which has been held since the beginning of the pandemic by combining e-training. This implementation had several obstacles including internet connection and there were still some participants who did not have adequate gadgets. The implementation of this training was supported by the replacement of internet quota fees that could support blended learning and LMS training.